Peningkatan Minat Belajar Matematika Melalui Pendekatan Technological Pedagogical And Content Knowledge (TPACK) Pada Siswa Kelas II SD - Maya Hilma Khoirunnisa; Diana Ermawati; Imada Khairunisa (Jurnal Profesi Pendidikan, 2025)
The problem addressed in this research is the low interest in mathematics learning among second-grade students at SDN Demangan, which is attributed to conventional teaching methods and the minimal use of technology in the learning process. The purpose of this study is to enhance students' interest in mathematics by implementing the Technological, Pedagogical, and Content Knowledge (TPACK) approach. This study employed Classroom Action Research (CAR) using the spiral model developed by Kemmis and McTaggart, which includes planning, action, observation, and reflection stages. The research was conducted in two cycles during the even semester of the 2024/2025 academic year. Data were collected using observation and a learning interest questionnaire and analyzed using the Guttman Scale in percentage form. The results indicated a significant improvement in students' learning interest: in the pre-cycle stage, student interest was at 45% (categorized as sufficient), increased to 70% in the first cycle (high category), and reached 87% in the second cycle (very high category). The application of the TPACK approach successfully created a more engaging and enjoyable learning environment, encouraging student participation. This study concludes that the TPACK approach is effective in increasing the interest of second-grade students in mathematics learning at Demangan Elementary School, Kudus.